The Role of Victim–Offender Alcohol Abuse on Crime Commission Process Involved in Sexual Victimization - Chopin, Julien (Victims & offenders, 2022)
This study investigates the role of alcohol consumption on the choices, decisions, and actions taken by the offenders during the crime-commission process. Specifically, this research aims to compare four different situations: neither the offender nor victim consumed alcohol, only the victim consumed alcohol, only the offender had consumed alcohol, and both the offender and victim had consumed alcohol. The sample used in this study consists of 2544 cases of extrafamilial assault involving adult victims in France. Bivariate and multivariate analyses are performed to examine the differences between the cases where neither offender nor victim consumed alcohol (n = 1259), only victims consumed alcohol (n = 241), only offenders consumed alcohol (n = 822), and both offenders and victims consumed alcohol (n = 222). Findings indicate that strong differences exist in the crime-commission process of sex offenders depending on both the victim and the offender’s alcohol consumption. We observed that decisions made during each phase (i.e., precrime, crime, and postcrime phases) of the crime were influenced by alcohol intoxication.